Nonverbal ways of communication and fiction (Eurasian Journal of Philology Science and Education, 2016)
The article considered with the nonverbal ways of communication problem. It represents the justification of the scientific project devoted to studying of nonverbal signs stylistic function in fiction. The author objectifies the thought that people and nation mutual understanding assumes not only learning of languages, but also understanding of the nationalcultural codes giving information about native speakers and the available special ways of crosscultural communication. As object of the research planned within the project is defined the nonverbal communication as a specific ethno cultural phenomenon, and as a subject – its national specifics in dia logue of cultures, in particular – the nonverbal means of communication reflected in works of Kazakh, Russian and English writers. Use of originals and translations of works, certainly, will form the basis of a number of con trastive aspects consideration.
Keywords: nonverbal signs; stylistic function; people and nationmutual understanding; native speakers; cultural national codes; crosscultural communication; specific ethnocultural phenomenon; nonverbal communication